2010
DOI: 10.1093/brain/awq250
|View full text |Cite
|
Sign up to set email alerts
|

Demyelination versus remyelination in progressive multiple sclerosis

Abstract: The causes of incomplete remyelination in progressive multiple sclerosis are unknown, as are the pathological correlates of the different clinical characteristics of patients with primary and secondary progressive disease. We analysed brains and spinal cords from 51 patients with progressive multiple sclerosis by planimetry. Thirteen patients with primary progressive disease were compared with 34 with secondary progressive disease. In patients with secondary progressive multiple sclerosis, we found larger brai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
187
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 270 publications
(199 citation statements)
references
References 44 publications
10
187
1
1
Order By: Relevance
“…Different relapses with similar phenotypes are typical. This situation is explained by the presence of new demyelination regions on or close to former remyelination regions (32,34).…”
mentioning
confidence: 99%
“…Different relapses with similar phenotypes are typical. This situation is explained by the presence of new demyelination regions on or close to former remyelination regions (32,34).…”
mentioning
confidence: 99%
“…It is most likely that the 2 streams of therapy will work in concert to synergistically increase outcome measures for MS patients. This is particularly important because remyelinated areas in MS are subject, and indeed they are more prone, than normal-appearing white matter to new inflammatory demyelination [38]. There are many avenues aimed to directly promote myelin repair, as well as the emergence of techniques available to quantitate remyelination in MS patients.…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, extensive remyelination was not limited to RRMS, but also in certain patients with more progressive disease [50]. A more recent study has reported that primary progressive MS patients tend to have greater remyelination capacity than those with secondary progressive disease [38]. Intensive sampling of tissue from 2 patients with >20 years disease activity revealed that 95 % of all lesions showed at least partial remyelination, furthermore supporting that some patients tend to extensively remyelinate despite chronic disease [44].…”
Section: Endogenous Remyelination In Ms Patientsmentioning
confidence: 91%
See 1 more Smart Citation
“…Oligodendrocytes are cells that produce myelin sheaths that insulate axons of neurons, enabling saltatory conduction between the Nodes of Ranvier for rapid propogation of action potential. These cells are targets of severe developmental diseases such as PelizaeusMerzbacher disease, and demyelinating diseases such as multiple sclerosis and CharcotMarie-Tooth (Bramow et al, 2010, Garbern, 2007, Sargiannidou et al, 2009. Dysfunctional oligodendrocytes in these diseases lead to disruptions in axonal transport.…”
Section: Glial Differentiation Of Hescsmentioning
confidence: 99%